Pernikahan Dini dan Kejadian Stunting di Desa Harimau Tandang - Hizazun Niswah; Ghita Apriani; Rizma Adlia Syakurah (Politeknik Negeri Jember, 2023)
Indonesia occupies the 5th position with the number of children with short stature in the world. The prevalence of stunting in Indonesia is still relatively high, reaching 30% – 39%, exceeding the WHO standard of only 20%. Stunting is a multifactorial health problem. The main causes of stunting are maternal and environmental factors. Marriage at an early age has an impact on the health of mothers and toddlers. This study aims to determine the relationship between early marriage and the incidence of stunting in Harimau Tandang Village, Kec. South Pemulutan, Kab. Ogan Ilir. This research is included in a quantitative study using a cross-sectional design. The research was conducted in Harimau Tandang Village from May 24 – June 20, 2022, using interview and observation methods. The population in this study were all mothers in Harimau Tandang Village who had children aged 0-59 months, using a sample of 40 mothers. Samples were taken using the purposive sampling technique. The analysis used in univariate and bivariate analyses with a significance level of 95%. Based on the results of the analysis, it can be seen that from 40 respondents, there were 12 people (30.0%) who married early and 28 people (70.0%) who did not marry early. There were 2 children aged 0-59 months in Harimau Tandang Village (5.0%) and 38 people (95.0%). The 12 mothers who married early, none had stunting children, meanwhile, of the 28 mothers who did not marry early, there were 2 mothers with stunting children and 26 mothers with non-stunted children. The results of the Fisher Exact test analysis show that the p-value = 1,000 (> 0.05). There is no relationship between early marriage and the incidence of stunting in Harimau Tandang Village, Kec. South Pemulutan, Kab. Ogan Ilir.